Effect of Nigeria’s Petroleum and Solid Mineral Exports to South Africa on Real GDP Growth in Nigeria - Ogechi Hope Njoku Njoku; Chibuike R. Oguanobi; Okpala Theodore Emenike (Paspama Institute, 2026)
This paper has explored how Nigeria exports of petroleum and solid minerals to South Africa impacted the growth of real GDP in Nigeria. The research was inspired by the necessity to assess how bilateral trade in the key natural resources can lead to the economic performance and the export diversification agenda of Nigeria. The paper was based on the Import-Led Growth (ILG) and Export-Led Growth (ELG) theories which predict the stimulating role that imports and exports play in economic growth. ILG points out that the imports of machinery, technology and intermediate goods enhance productivity, industrial capacity and competitiveness. ELG argues that exports will create foreign exchange, enhance balance of payment and boost output. The paper applied a modified Cobb-Douglas production model to identify an ARDL model to explore the relationship between Nigeria petroleum and solid mineral exports to South Africa and the GDP growth. The data were analyzed using E-Views 10 based on quarterly data (19962023) of the following sources; WITS, WDI, WGI, CBN and NBS. According to the correlation matrix, multicollinearity among the variables is not serious since the coefficients are moderate and below critical values, which confirm that it is appropriate to be estimated. The ARDL bounds test gave F-statistic value of 4.249006, which is greater than the upper limit of 3.38 (5 percent) which demonstrates that the variables are in a long-run relationship. The long-run outcomes indicate that petroleum exports have a tremendous and positive effect on the real GDP of Nigeria, whereas solid minerals exports are not substantial. Institutional quality has a large negative impact in the short-run and petroleum exports are positive but not significant. The lack of autocorrelation and heteroscedasticity is established by diagnostic tests, and the overall model stability and reliability is provided by the CUSUM test. The paper found that petroleum exports continue to be at the heart of economic development in Nigeria, but that the solid minerals industry is poorly developed and under exploited. The research advised the diversification of the export income by strategic investment in the solid minerals sector, institutional quality, mining infrastructure, and intensified relations in trade with South Africa in a way that would result in sustainable growth.